(untitled) (The Planet, 2024)
Introduction: Otitis Media with Effusion (OME) remains a significant public health concern in Bangladesh, particularly affecting the pediatric population. This study aimed to analyze the clinical profile and outcomes of different treatment modalities in patients presenting with OME at Holy Family Red Crescent Medical College Hospital. Methods & Materials: A prospective observational study was conducted on 60 patients diagnosed with OME between January 2023 and December 2023. Patients underwent comprehensive clinical examination including otoscopy, tympanometry, and pure tone audiometry. Treatment included both medical and surgical interventions, with follow-up periods ranging from 6 to 12 months. Results: The study population comprised 58.3% males and 41.7% females, with 70% of patients aged 3-12 years. Hearing impairment was the predominant symptom (85%), followed by ear fullness (65%). Upper respiratory tract infections were the most common associated factor (75%). Medical management alone was successful in 70% of cases, while surgical intervention, required in 30% of cases, showed an 88.9% success rate. The mean air-bone gap improved from 28.5 ± 5.2 dB pre-treatment to 12.3 ± 4.1 dB post-treatment (p < 0.001). The recurrence rate was 11.7%, primarily associated with persistent allergic rhinitis. Conclusion: This study demonstrates that a systematic approach to OME management, incorporating both medical and surgical interventions as appropriate, yields favorable outcomes in the Bangladeshi population. The findings emphasize the importance of early intervention and regular follow-up in achieving optimal results, particularly in pediatric cases. The high success rates observed support the implementation of standardized treatment protocols while considering individual patient factors.